PERBAIKAN GENETIK ANGGREK ALAM Vanda spp MELALUI PERSILANGAN INTERSPESIFIK DALAM MENDUKUNG PERKEMBANGAN ANGGREK DI INDONESIA - Sri Hartati; Sumijati Sumijati; Pardono Pardono; Ongko Cahyono (Caraka Tani: Journal of Sustainable Agriculture, 2014)
Efforts to improve the genetic quality of orchids have constraints on seed propagation techniques crosses and from crosses. The study aims to: (1) obtain a cross technique that can produce seeds with high fertility rates, (2) to obtain a new hybrid character which has advantages in flower. The study was conducted at the Center for Plant Conservation Kebun Raya Bogor LIPI. Research was an interspecific crosses that ♀ Vanda celebica x ♂ Vanda tricolor, ♀ Vanda celebica x ♂ Vanda dearei, ♀ Vanda celebica x ♂ Vanda insignis. And crosses the reciprocal is ♀ Vanda tricolor x ♂ Vanda celebica, ♀ Vanda dearei x ♂Vanda celebica, ♀ Vanda insignis x ♂Vanda celebica. Crosses performed by crossing parent elected as male or female parent. Activities include characterization of elders, crosses, harvesting, seed dispersal, seed Deployment and transfer done aseptically in tissue culture laboratory. Observations included the successful crossing, when formed fruit, ripe fruit, and formed protokorm. Of research produced 5 series hybrid to form protokorm is Vanda dearei x Vanda Celebica, Vanda celebica x Vanda dearei, Vanda insignis x Vanda celebica, Vanda celebica x Vanda insignis, Vanda celebica x Vanda tricolo. The success of crosses 33%- 100%, time required for seed maturation varies between 122-262 days, 16-23 days old germinated.